Self-Assessment Techniques in Clinical Studies in Public Universities in Anambra State: Benefits and Alignment With Supervisors Evaluation as Perceived by Medical Students - Nneka Chinyere Ezeugo; Lydia Ijeoma Eleje; Gideon Ebuka Obiasor; Njideka Gertrude Mbelede; Kalu Eke Osonwa; Ifeoma Clementina Metu; George Uchenna Eleje (Journal of Medical Education and Curricular Development)
OBJECTIVES This research explores the perceptions of medical students regarding self-assessment techniques in clinical studies at public universities in Anambra State, Nigeria. Specifically, it investigates the benefits of these techniques and their perceived alignment with formal evaluations conducted by supervisors. METHODS Utilizing a descriptive cross-sectional study design, data were collected from 273 consenting medical students through an online questionnaire. The questionnaire was developed to capture students’ demographics, experiences with self-assessment, and perceptions of its benefits in relation to supervisor evaluations. RESULTS Results indicate a balanced representation of gender among respondents, with the majority falling within the 21‒25 years’ age range, and nearly equal participation from students at the 500 and 600 levels across two institution types, Federal and State. The findings reveal a positive alignment between students’ perception of self-assessments and formal evaluations, with no significant discrepancies observed between institutions or levels of study. Additionally, participants widely perceive self-assessment as beneficial for enhancing confidence, identifying learning gaps, fostering professional growth, and improving communication skills. Furthermore, students from both institutions and across different levels of study report similar perceived benefits from engaging in self-assessment practices. CONCLUSIONS There is a strong alignment between medical students’ perceptions of self-assessments and formal evaluations, with no significant differences found across institutions or stages of study. Overall, self-assessment was viewed as valuable for boosting confidence, identifying areas for improvement, supporting professional development, and enhancing communication skills. Further exploration of students’ perspectives will offer valuable insights for educators to design effective learning strategies and promote lifelong learning habits among medical students.